2019
DOI: 10.1080/13698575.2019.1640352
|View full text |Cite
|
Sign up to set email alerts
|

Birth models in and between Italy and Senegal: a cross-cultural inquiry on the risks related to childbirth and birth technologies

Abstract: In Western societies, such as Italy, a positive representation of birth technologies as the main remedy to fight against the uncertainties of physiology and biological risks associated with pregnancy and childbirth has prevailed since the eighteenth century. This process has experienced a strengthening and an acceleration in the last fifty years. Although the (bio)medical discourse has replaced previous representations of childbirth-related risks, other risk categorizations, and search for remedies, have emerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…However, since the 2010s, the physiological approach, built around the idea of nature, has become increasingly prevalent, spread by user associations that are active in the public debate. As shown in Italy ( Quagliariello, 2019 ), the majority of women in France continue to give birth in hospital, including women who promote a critical discourse on the use of biotechnology during childbirth. This research has shown that in maternity settings, the reference to nature is very present, even among women who have accepted the biomedical model as they give birth in a maternity hospital rather than a birthing centre.…”
Section: Discussionmentioning
confidence: 99%
“…However, since the 2010s, the physiological approach, built around the idea of nature, has become increasingly prevalent, spread by user associations that are active in the public debate. As shown in Italy ( Quagliariello, 2019 ), the majority of women in France continue to give birth in hospital, including women who promote a critical discourse on the use of biotechnology during childbirth. This research has shown that in maternity settings, the reference to nature is very present, even among women who have accepted the biomedical model as they give birth in a maternity hospital rather than a birthing centre.…”
Section: Discussionmentioning
confidence: 99%
“…This latter group of women represent however a minority within the alternative birth hospital in Tuscany which itself is a minority case within the Italian obstetrical landscape. Yet the Senegalese women in Quagliariello's (2019) study, most of whom were of low or middle SES, also displayed a critical reflexivity despite their fascination for some of the techniques. They considered amniocentesis in a negative way, as they saw it as risky, either because they had heard about risks of miscarriage associated to it, or because they believed more generally that it can provoke extra-biological risks by attracting the 'evil agents' interested in 'eating' the amniotic liquid.…”
Section: Access To Technology and Ambivalences Around Riskmentioning
confidence: 90%
“…Jordanian women of low or middle SES also appeared to be quite critical about acceleration of labour and episiotomy as they feared their iatrogenic risks, whereas they saw the access to ultrasound or monitoring devices as an entry to modern and state-funded services, and even as a way to be treated as real citizens. Quagliariello (2019) similarly shows in this issue, drawing on the case of the Senegalese women who migrated to Italy, that they expected and hoped to access to pregnancy and birth technologies such as ultrasound, electronic monitoring devices or epidural anaesthesia. Because these material opportunities can only be afforded by upperclass women in their home country, they seemed to consider access to these as luxury health care, but also as a demonstration of the fact that they are being treated normallythat is to say without racist discriminationin their host country.…”
Section: Access To Technology and Ambivalences Around Riskmentioning
confidence: 92%
See 1 more Smart Citation
“…As previously discussed, IR was closely related to cultural issues. Therefore, it was essential to conduct the stream of cultural inquiry (CI) that could encourage and unify the measures taken by the members of different groups to reach common goals, such as the management of an organization or institution in the corporate industry in China (Xing et al 2016 ), as well as to achieve social justice, particularly in education, through the understanding and appreciation of different behavior and culture (Murrell 2006 ; Quagliariello 2019 ). The efforts to realize togetherness in pluralism required a cross-cultural collaboration (Spires et al 2018 ).…”
Section: Literature Reviewmentioning
confidence: 99%